E-waste management: an emerging global crisis and the Malaysian scenario - Alias, Ahmad Faisal; Ishak, Mohd Bakri; Mohamad Zulkifli, Siti Nur Awanis; Abdul Jalil, Rusamah (Integrated Publishing Association, 2014)
Rapid progress in standard of living and advances in information and communication technology (ICT) has generated an enormous amount of end of life electrical and electronic equipment which eventually become e-waste. Although it represents a small percentage of total solid waste, e-waste is the fastest growing waste stream in the world, with most of them flowing from developed to developing countries for the purpose of recovery and recycling activities. However, poor recovery and recycling facilities produce toxic residues which were eventually landfilled or openly incinerated with severe negative effects on human and environmental health. Although the Basel Convention and other legislations were introduced by nations to limit the global trans-boundary shipment of the highly toxic e-waste, the illicit trade is difficult to trace and regulate due to multiple loopholes. Consequently, only a small fraction of generated e-waste finds its way to licensed material recovery facilities (MRFs) for recycling purposes, while the rest is recovered by the informal sector in the developing countries. One of latest e-waste reduction strategies introduced is the extended producer responsibility. Although the issue of e-waste is quite new in Malaysia, the country is also grappling with the crisis and has become one the main destinations of the global e-waste trade.